P96 Death related to cardiovascular disease in chronic obstructive pulmonary disease. (15th November 2017) - Fermont, JM; Wood, AM; Müllerova, H; Wilkinson, IB
Abstract : Chronic obstructive pulmonary disease (COPD) kills over 5.6% (3.2 million) of the world population every year and is projected to increase to 7.8% by 2030. According to the literature about a third of patients with COPD die of cardiovascular disease (CVD). However, these findings do not match clinical data from the Evaluating the Role of Inflammation in Chronic Airways disease (ERICA) cohort − a multi-centre observational cohort study of 729 patients with COPD − nor published data from the late 60 s indicating only about a tenth of patients dying of CVD. The aim of our study was to categorise causes of death, and compare self-reported CVD incidence with electronic health records. Clinical data were linked to mortality data from the Office for National Statistics. Causes of death were categorised by cardiovascular and respiratory physicians. Self-reported cardiovascular events were compared with hospital episode statistics. Results indicate that after 5 years of follow-up, a majority of deaths (n=119) are due to pulmonary causes (53%), followed by cancer (24%) with fewer cases than expected having a cardiac cause of death (14%). Eight per cent died of other causes. In addition, there were only few severe cardiovascular events such as stroke and heart attack. It might be that globally the cause of death within COPD has changed over several decades with increased numbers of cardiac causes of deaths but our findings do not indicate as many cardiac deaths and this trend might at least exclude the UK and warrants further exploration.